On the Nature of the Cost-Benefit Schedule - Jones, Carl R. (Management Science, 1971)
In this paper the nature of a set of coat-benefit studied alternatives is studied. An integrated set of submodels is assumed to provide the foundation for a cost-benefit schedule. The model is formulated as an efficiency problem using the technique of vector maximization. Efficient points are characterized by a set of decision rules. A local cost-benefit function is developed. Comparative statics (sensitivity analysis) results show that there exist efficiency substitution and benefit effects. These effects are the basis for rigorous definitions of efficiency substitutes and complements.